Changing returns to education during a boom? The case of Ireland - Seamus McGuinness; Frances McGinnity; Philip O'Connell (The Economic and Social Research Institute (ESRI), 2008)
Ireland's 'Celtic Tiger' years saw GDP per capita rise from 60% of the EU average to 120% of the average over the course of the 1990s, with a growth in employment of about 40% over the period 1994-2001. What were the consequences of the boom for returns to education and wage inequality? This paper uses data from the Living in Ireland Survey for 1994, 1997 and 2001 to examine wage inequality, the returns to education and the relative demand for labour for men and women. Theories of skilled-biased technical change suggest that the rapid period of economic growth experienced in Ireland will have been accompanied by a rise in the relative demand for skilled labour that will, in turn, have led to rising wage inequality. However, this is not the case for this period. We find fairly stable returns to education and falling wage inequality for men throughout the period, partly explained by a rapid growth in demand for unskilled labour, which helped maintain low-skilled wages. For women we find some fall in the wage premium to a university degree and falling wage inequality in the period 1997-2001. We argue that for women, low-skilled wages were kept up by the introduction of the minimum wage in 2000, and high skilled wages fell due to a rapid rise in the supply of highly qualified women. The Irish example shows that skill-biased technical change theory needs to take account of both the specific changes in the nature of labour demand and the nature and extent of concomitant changes in labour supply.
Keywords: I2; J21; J23; J24; J30; J31; 330; earnings inequality; returns to education; gender; Ireland; Bildungsertrag; Qualifikation; Lohndifferenzierung; Geschlecht; Irland